2021
DOI: 10.1038/s41533-021-00227-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and factors associated with triple therapy use in newly diagnosed patients with COPD

Abstract: There is limited information about the initiation of triple therapy (TT) in patients with chronic obstructive pulmonary disease (COPD) in primary care. This was an observational, population-based study in patients identified from a primary care electronic medical records database in Catalonia from 2011 to 2015 aimed to identify the use of TT in patients with newly diagnosed COPD. A total of 69,668 newly diagnosed patients were identified of whom 11,524 (16.5%) initiated TT, of whom 8626 initiated TT at or imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Our results concur with other recent studies that confirmed the association between symptoms and ICS prescription. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results concur with other recent studies that confirmed the association between symptoms and ICS prescription. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Our results concur with other recent studies that confirmed the association between symptoms and ICS prescription. 29,30 Understanding the role of eosinophils in COPD has increased over the last years. 31 Within our sample, blood eosinophils were not associated with ICS use, which in addition to the significant proportion of patient with missing eosinophil counts, could be suggesting a lack of awareness of the usefulness of eosinophil counts for the management of COPD within primary care.…”
mentioning
confidence: 99%
“…In an international multicenter study, the median time from initial COPD diagnosis to the first prescription of triple therapy ranged from 16.9 (5.7–36.2) months in Australia to 42.5 (13.9–87.4) months in the UK [ 24 ]. The most common treatment pathways to triple therapy initiation are starting with ICS/LABA, no therapy, LAMA alone, [ 24 , 69 ] and LABA/LAMA [ 70 ]. A real-world study observed that patients who did not had exacerbations in the previous year often received ICS-containing therapy before escalation to triple therapy.…”
Section: Key Questions In Using Sitt In Oadmentioning
confidence: 99%
“…Current GOLD guidelines recommend TT for severe disease, frequent exacerbations and persistent symptoms who were not adequately controlled with LABA/LAMA or ICS/LABA therapy [ 19 ]. However, several real-world studies reported progression to TT even in patients with no exacerbations in the previous year [ 69 ]. L andis et al .…”
Section: Key Questions In Using Sitt In Oadmentioning
confidence: 99%
“… 9 Nevertheless, it remains surprising that many general practitioners prescribe triple therapy shortly after or even before an established COPD diagnosis. 10 , 11 Variables associated with ICS/LABA/LAMA therapy initiation in newly diagnosed patients with COPD were FEV 1 , exacerbations, male sex, increased age, current or previous smoking, and some comorbid lung conditions in US 10 and male sex, older age, previous exacerbations, asthma-COPD overlap, a previous treatment regimen containing an ICS, previous pneumonia, and history of lung cancer in Spain. 11 However, the transition to triple therapy in those already on regular treatment for COPD, which is not necessarily a LABA/LAMA combination, follows pathways that are influenced by many different factors that vary both within and between countries probably due to differences in prescribing practices.…”
Section: Introductionmentioning
confidence: 99%